Uniform deposition of coupled CdS and CdSe quantum dots on ZnO nanorod arrays as electrodes for photoelectrochemical solar water splitting. (21st January 2015) - Lin, Chin-Jung; Kao, Li-Cheng; Huang, Yu; Bañares, Miguel A.; Liou, Sofia Ya-Hsuan
Abstract A modified successive ionic layer adsorption and reaction (SILAR) process was used for deposition of coupled CdS and CdSe quantum dots (QDs) on the surface of orientated ZnO nanorod arrays. This solution-based process provides a conformal and homogeneous QDs deposition along the ZnO nanorod arrays with no entry clogging. The prepared multi-heterojunction CdSe/CdS/ZnO nanorod-arrayed photoanodes are highly visible-light-sensitive and show improved ion diffusion and effective suppression of electron–hole pair recombination. For photoeletrochemical solar water splitting, the photoanode prepared using the modified SILAR outperformed that using the conventional SILAR by >15% improvement in solar-to-hydrogen conversion efficiency.